Ionic gel and preparation method thereof

By introducing physical crosslinked microspheres and/or chemical crosslinked microspheres into the ionic gel to adjust their proportions, the problems of low mechanical strength and poor toughness of the ionic gel are solved, and the optimization of its mechanical properties and stability enhancement are achieved.

CN119798549APending Publication Date: 2025-04-11GREATER BAY AREA UNIV (IN PREPARATION)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411885118.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing ionic gels have problems with low mechanical strength and poor toughness, which are difficult to adapt to different application environments and needs.

Method used

The proportions are adjusted to enhance the mechanical strength and stability of the gel by introducing physically crosslinked microspheres and/or chemically crosslinked microspheres into the ionic gel.

Benefits of technology

The mechanical properties of the ion gel are optimized, which enhances its mechanical strength and stability, allowing it to adapt to different application environments and needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005199107810000091
    Figure BDA0005199107810000091
Patent Text Reader

Abstract

The invention relates to the technical field of ionic gel, and particularly discloses ionic gel and a preparation method thereof. The ionic gel comprises the following raw materials in parts by weight: 20-40 parts of a monomer, 10-50 parts of an ionic solution and 0.1-5 parts of cross-linked microspheres, the cross-linked microspheres comprise at least one of physical cross-linked microspheres and chemical cross-linked microspheres. The ionic gel prepared by the invention has excellent mechanical regulatable performance, and the mechanical strength and stability of the ionic gel are enhanced by selecting physical crosslinking microspheres and / or chemical crosslinking microspheres, so that the ionic gel can adapt to different application environments and requirements. Wherein the toughness and the strength of the gel can be effectively enhanced by adjusting the ratio of the physical crosslinking microspheres to the chemical crosslinking microspheres.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ion gel, and in particular to an ion gel and a preparation method thereof. Background Art

[0002] Ion gels are composed of ionic liquids and high molecular organic polymers. In recent years, compared with traditional hydrogels, ion gels have high stability, high ionic conductivity, non-flammability and non-volatility. These characteristics have gradually attracted attention and are widely used in ion gel electrolytes, ion skins, soft electronics and adhesives.

[0003] Mechanical properties are one of the key parameters for the application of ion gels. However, most ion gels to date have problems such as low strength and poor toughness. Reasonable structural design and the introduction of effective energy dissipation mechanisms are crucial to improving the mechanical properties of gels. At present, chemical crosslinking or physical crosslinking is often formed by introducing double networks, phase separation, supramolecular interactions, etc. to improve the mechanical properties of gels. Among them, the deformable crosslinked network of microspheres can be used in the physical or chemical crosslinking area to effectively dissipate the stress concentration at the crack tip and improve the mechanical properties of the material.

[0004] Therefore, it is necessary to provide an ion gel and a preparation method thereof to enhance the mechanical strength and stability of the ion gel so that the ion gel can adapt to different application environments and requirements. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides an ion gel and a preparation method thereof, which enhance the mechanical strength and stability of the ion gel so that the ion gel can adapt to different application environments and requirements.

[0006] A first aspect of the present invention provides an ion gel.

[0007] Specifically, the raw materials of the ion gel include 20 to 40 parts of monomers, 10 to 50 parts of ion solution, and 0.1 to 5 parts of cross-linked microspheres, by weight.

[0008] The cross-linked microspheres include at least one of physically cross-linked microspheres and chemically cross-linked microspheres.

[0009] Preferably, the raw materials of the ion gel include 22 to 40 parts of monomers, 15 to 50 parts of ion solution, and 0.1 to 4.5 parts of cross-linked microspheres, in parts by weight.

[0010] Further preferably, the raw materials of the ion gel include 25 to 40 parts of monomers, 15 to 45 parts of ion solution, and 0.1 to 4 parts of cross-linked microspheres, in parts by weight.

[0011] Preferably, the raw material of the ion gel further includes at least one of an initiator and an accelerator.

[0012] Preferably, the monomer includes any one of acrylamide, N,N'-dimethylacrylamide, and hydroxyethyl methacrylate.

[0013] Preferably, the ionic solution includes any one of 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide, 1-ethyl-3-methylimidazolium ethylsulfonate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, and methyl tributylphosphonium dimethyl phosphate.

[0014] Preferably, the physically cross-linked microspheres include polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate.

[0015] Preferably, the chemically cross-linked microspheres include polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate.

[0016] Preferably, the initiator includes any one of ammonium persulfate and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

[0017] Preferably, the accelerator includes any one of tetramethylethylenediamine.

[0018] A second aspect of the present invention provides a method for preparing an ion gel.

[0019] Specifically, the following steps are included:

[0020] (1) adding monomers, cross-linked microspheres, ion solution, and water into a container and stirring;

[0021] (2) adding an accelerator and / or an initiator to obtain a mixed solution;

[0022] (3) pouring the mixed solution into a mold and allowing it to gel to obtain the ion gel.

[0023] Preferably, the water comprises deionized water.

[0024] Preferably, in step (1), the stirring time is 4 to 12 hours.

[0025] Further preferably, in step (1), the stirring time is 8 to 12 hours.

[0026] More preferably, in step (1), the stirring time is 12 hours.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0028] The ion gel prepared by the present invention has excellent mechanically controllable properties. By selecting physically cross-linked microspheres and / or chemically cross-linked microspheres, the mechanical strength and stability of the ion gel are enhanced, so that the ion gel can adapt to different application environments and needs. Among them, by adjusting the ratio of physically cross-linked microspheres and chemically cross-linked microspheres, the toughness and strength of the gel can be effectively enhanced. DETAILED DESCRIPTION

[0029] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0030] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0031] Example 1

[0032] An ion gel and a preparation method thereof.

[0033] Ion gel: the raw materials are 35 parts of acrylamide, 1 part of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate, 0.15 parts of ammonium persulfate, 0.84 parts of tetramethylethylenediamine, 35 parts of methyl tributylphosphonium dimethyl phosphate, and 28.01 parts of deionized water.

[0034] The preparation method is as follows:

[0035] (1) acrylamide, polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate, methyl tributylphosphine dimethyl phosphate, and deionized water were sequentially added into a glass container and magnetically stirred for 12 hours;

[0036] (2) During the stirring process, tetramethylethylenediamine and ammonium persulfate are added dropwise to prepare a mixed solution;

[0037] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0038] Example 2

[0039] An ion gel and a preparation method thereof.

[0040] The difference from Example 1 is that the ion gel raw material contains 3 parts of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate and 26.01 parts of deionized water.

[0041] The preparation method is the same as that in Example 1.

[0042] Example 3

[0043] An ion gel and a preparation method thereof.

[0044] The difference from Example 1 is that the ion gel raw material contains 21 parts of methyl tributylphosphonium dimethyl phosphate and 42.01 parts of deionized water.

[0045] The preparation method is the same as that in Example 1.

[0046] Example 4

[0047] An ion gel and a preparation method thereof.

[0048] Ion gel: the raw materials are 40 parts of acrylamide, 1 part of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate, 0.15 parts of ammonium persulfate, 0.84 parts of tetramethylethylenediamine, 15 parts of 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt, and 43.01 parts of deionized water.

[0049] The preparation method is as follows:

[0050] (1) acrylamide, polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate, 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt, and deionized water were sequentially added into a glass container and magnetically stirred for 12 h;

[0051] (2) During the stirring process, tetramethylethylenediamine and ammonium persulfate are added dropwise to prepare a mixed solution;

[0052] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0053] Example 5

[0054] An ion gel and a preparation method thereof.

[0055] Ion gel: the raw materials are 35 parts of acrylamide, 0.3 parts of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate, 0.15 parts of ammonium persulfate, 0.84 parts of tetramethylethylenediamine, 35 parts of methyl tributylphosphine dimethyl phosphate, and 28.71 parts of deionized water.

[0056] The preparation method is as follows:

[0057] (1) acrylamide, polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate, methyl tributylphosphine dimethyl phosphate, and deionized water were sequentially added into a glass container and magnetically stirred for 12 hours;

[0058] (2) During the stirring process, tetramethylethylenediamine and ammonium persulfate are added dropwise to prepare a mixed solution;

[0059] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0060] Example 6

[0061] An ion gel and a preparation method thereof.

[0062] The difference from Example 5 is that the ion gel raw material contains 0.7 parts of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate and 28.31 parts of deionized water.

[0063] The preparation method is the same as that of Example 5.

[0064] Example 7

[0065] An ion gel and a preparation method thereof.

[0066] The difference from Example 5 is that the ion gel raw materials include 40 parts of acrylamide, 25 parts of methyl tributylphosphonium dimethyl phosphate, and 33.71 parts of deionized water.

[0067] The preparation method is the same as that of Example 5.

[0068] Example 8

[0069] An ion gel and a preparation method thereof.

[0070] Ion gel: the raw materials are 35 parts of acrylamide, 1 part of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate, 0.3 parts of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate, 0.15 parts of ammonium persulfate, 0.84 parts of tetramethylethylenediamine, 35 parts of methyl tributylphosphine dimethyl phosphate, and 27.71 parts of deionized water.

[0071] The preparation method is as follows:

[0072] (1) acrylamide, poly(ethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate), poly(ethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate), methyl tributylphosphine dimethyl phosphate, and deionized water were sequentially added into a glass container and magnetically stirred for 12 h;

[0073] (2) During the stirring process, tetramethylethylenediamine and ammonium persulfate are added dropwise to prepare a mixed solution;

[0074] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0075] Example 9

[0076] An ion gel and a preparation method thereof.

[0077] The difference from Example 8 is that the ion gel raw material contains 45 parts of methyl tributylphosphonium dimethyl phosphate and 17.71 parts of deionized water.

[0078] The preparation method is the same as that of Example 8.

[0079] Example 10

[0080] An ion gel and a preparation method thereof.

[0081] Ion gel: The raw materials are 35 parts of N,N'-dimethylacrylamide, 1 part of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate, 3 parts of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate, 0.15 parts of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 35 parts of methyl tributylphosphonium dimethyl phosphate, and 25.85 parts of deionized water.

[0082] The preparation method is as follows:

[0083] (1) N,N'-dimethylacrylamide, poly(ethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate), poly(ethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate), methyl tributylphosphine dimethyl phosphate, and deionized water were sequentially added into a glass container and magnetically stirred for 12 h;

[0084] (2) During the stirring process, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone was added dropwise to prepare a mixed solution;

[0085] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0086] Embodiment 11

[0087] An ion gel and a preparation method thereof.

[0088] Ion gel: The raw materials are 26 parts of acrylamide, 9 parts of hydroxyethyl methacrylate, 1 part of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate, 0.3 parts of polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate, 0.15 parts of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, 35 parts of methyl tributylphosphine dimethyl phosphate, and 28.55 parts of deionized water.

[0089] The preparation method is as follows:

[0090] (1) acrylamide, hydroxyethyl methacrylate, polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate, polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate, methyl tributylphosphine dimethyl phosphate, and deionized water were sequentially added into a glass container and magnetically stirred for 12 hours;

[0091] (2) During the stirring process, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone was added dropwise to prepare a mixed solution;

[0092] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0093] Comparative Example 1

[0094] An ion gel and a preparation method thereof.

[0095] Ion gel: the raw materials are 35 parts of acrylamide, 2 parts of N,N'-methylenebisacrylamide, 0.15 parts of ammonium persulfate, 0.84 parts of tetramethylethylenediamine, 35 parts of methyltributylphosphonium dimethyl phosphate, and 27.01 parts of deionized water.

[0096] The preparation method is as follows:

[0097] (1) acrylamide, N,N'-methylenebisacrylamide, methyl tributylphosphine dimethyl phosphate, and deionized water were sequentially added into a glass container and magnetically stirred for 12 hours;

[0098] (2) During the stirring process, tetramethylethylenediamine and ammonium persulfate are added dropwise to prepare a mixed solution;

[0099] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0100] Comparative Example 2

[0101] An ion gel and a preparation method thereof.

[0102] Ion gel: the raw materials are 40 parts of acrylamide, 2 parts of N,N'-methylenebisacrylamide, 0.15 parts of ammonium persulfate, 0.84 parts of tetramethylethylenediamine, 15 parts of 1-butyl-3-methylimidazolium tetrafluoroborate, and 42.01 parts of deionized water.

[0103] The preparation method is as follows:

[0104] (1) acrylamide, N,N'-methylenebisacrylamide, 1-butyl-3-methylimidazolium tetrafluoroborate, and deionized water were sequentially added into a glass container and magnetically stirred for 12 h;

[0105] (2) During the stirring process, tetramethylethylenediamine and ammonium persulfate are added dropwise to prepare a mixed solution;

[0106] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0107] Comparative Example 3

[0108] An ion gel and a preparation method thereof.

[0109] Ion gel: the raw materials are 40 parts of hydroxyethyl methacrylate, 2 parts of N,N'-methylenebisacrylamide, 0.15 parts of ammonium persulfate, 0.84 parts of tetramethylethylenediamine, 41 parts of 1-ethyl-3-methylimidazolium ethyl sulfonate, and 16.01 parts of deionized water.

[0110] The preparation method is as follows:

[0111] (1) Hydroxyethyl methacrylate, N,N'-methylenebisacrylamide, 1-ethyl-3-methylimidazolium ethyl sulfonate, and deionized water were sequentially added into a glass container and magnetically stirred for 12 h;

[0112] (2) During the stirring process, tetramethylethylenediamine and ammonium persulfate are added dropwise to prepare a mixed solution;

[0113] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0114] Comparative Example 4

[0115] An ion gel and a preparation method thereof.

[0116] Ion gel: The raw materials are 21 parts of acrylamide, 14 parts of N,N'-dimethylacrylamide, 2 parts of N,N'-methylenebisacrylamide, 0.15 parts of ammonium persulfate, 0.84 parts of tetramethylethylenediamine, 35 parts of 1-butyl-3-methylimidazole hexafluorophosphate, and 27.01 parts of deionized water.

[0117] The preparation method is as follows:

[0118] (1) acrylamide, N,N'-dimethylacrylamide, N,N'-methylenebisacrylamide, 1-butyl-3-methylimidazolium hexafluorophosphate, and deionized water were sequentially added into a glass container and magnetically stirred for 12 h;

[0119] (2) During the stirring process, tetramethylethylenediamine and ammonium persulfate are added dropwise to prepare a mixed solution;

[0120] (3) Pour the mixed solution into a mold, cover it with a glass slide, and leave it at room temperature overnight to form a gel to obtain an ion gel.

[0121] Mechanical properties test of ion gel: The mechanical properties of all dumbbell-shaped hydrogel samples (length 50 mm, gauge length 20 mm, thickness 2 mm, width 4 mm) were tested using a universal testing machine (Instron, 68TM-30), which was equipped with a 100N sensor and a 250N pneumatic clamp, with a tensile speed of 50 mm / min. The test can obtain a stress-strain curve. The tensile modulus is calculated from the linear fitting slope between 0 and 10 strains in the stress-strain curve; the elongation at break is the strain value of the stress sudden drop (i.e., sample fracture) in the stress-strain curve; the maximum tensile stress is the maximum stress in the stress-strain curve; and the tensile strength is the area of ​​the stress-strain curve.

[0122] Table 1 Mechanical properties of ion gels prepared in Examples 1 to 4

[0123] Example 1 Example 2 Example 3 Example 4 Elastic modulus(KPa) 58.76 59.13 121.15 202.86 Breaking strength(KPa) 55.1 79.5 65.3 89.2 Fracture strain (%) 2867.71 2463.37 1582.90 1444.70

[0124] It can be seen from Table 1 that the ion gel containing physically cross-linked microspheres prepared in Examples 1 to 4 of the present invention has good mechanical ductility.

[0125] Table 2 Mechanical properties of ion gels prepared in Examples 5 to 7

[0126] Example 5 Example 6 Example 7 Elastic modulus(KPa) 76.17 68.78 53.79 Breaking strength(KPa) 254 241.2 117.8 Fracture strain (%) 2155.10 1693.97 2472.24

[0127] As can be seen from Table 2, the ion gels containing chemically cross-linked microspheres prepared in Examples 5 to 7 of the present invention have better mechanical ductility and are stronger than the ion gels containing physically cross-linked microspheres prepared in Examples 1 to 4.

[0128] Table 3 Mechanical properties of ion gels prepared in Examples 8 to 11

[0129]

[0130]

[0131] As can be seen from Table 3, the ionic gels prepared in Examples 8 to 11 of the present invention, which contain both physically crosslinked microspheres and chemically crosslinked microspheres, enhance the overall mechanical properties. At the same time, the mechanical properties of the ionic gels formed by monomers and ionic liquids with different hydrophilicity and hydrophobicity vary greatly.

[0132] Table 4 Mechanical properties of ion gels prepared in Comparative Examples 1 to 4

[0133] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Elastic modulus(KPa) 144.08 176.77 119.27 55.5 Breaking strength(KPa) 451.9 672.5 65.1 145.8 Fracture strain (%) 650.91 812.88 85.42 717.24

[0134] As can be seen from Table 4, the N,N'-methylenebisacrylamide cross-linked ion gels prepared in Comparative Examples 1 to 4 can show the mechanical performance advantages of using microspheres as physical / chemical cross-linking of ion gels. Microspheres can improve the mechanical properties of the ion gel of the corresponding monomer in the ionic liquid as a whole, and can also flexibly adjust the mechanical conditions of the ion gel.

[0135] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.

Claims

1. An ion gel, characterized in that: The raw materials of the ion gel include 20 to 40 parts of monomers, 10 to 50 parts of ion solution, and 0.1 to 5 parts of cross-linked microspheres by weight; The cross-linked microspheres include at least one of physically cross-linked microspheres and chemically cross-linked microspheres.

2. The ion gel according to claim 1, characterized in that The raw materials of the ion gel also include at least one of an initiator and an accelerator.

3. The ion gel according to claim 1, characterized in that The monomer includes any one of acrylamide, N,N'-dimethylacrylamide and hydroxyethyl methacrylate.

4. The ion gel according to claim 1, characterized in that The ionic solution includes any one of 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt, 1-ethyl-3-methylimidazolium ethylsulfonate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, and methyl tributylphosphonium dimethyl phosphate.

5. The ion gel according to claim 1, characterized in that The physically cross-linked microspheres include polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate.

6. The ion gel according to claim 1, characterized in that The chemically cross-linked microspheres include polyethyl acrylate-methacrylic acid-dimethyl biphenyl dicarboxylate-glycidyl methacrylate.

7. The ion gel according to claim 1, characterized in that The initiator includes any one of ammonium persulfate and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

8. The ion gel according to claim 1, characterized in that The accelerator includes any one of tetramethylethylenediamine.

9. The method for preparing the ion gel according to any one of claims 1 to 8, comprising the following steps: (1) adding monomers, cross-linked microspheres, ion solution, and water into a container and stirring; (2) adding an accelerator and / or an initiator to obtain a mixed solution; (3) pouring the mixed solution into a mold and allowing it to gel to obtain the ion gel.

10. The preparation method according to claim 9, characterized in that: In step (1), the stirring time is 4 to 12 hours.

Citation Information

Patent Citations

  • Preparation method of nano composite hydrogel based on polymer nano microsphere hydrogen bond crosslinking

    CN109851815A

  • High-strength ionic liquid gel and preparation method thereof

    CN111533847A

  • Preparation method of ionic liquid gel microspheres and application of ionic liquid gel microspheres as liquid chamber microreactor in oil desulfurization

    CN115636957A

  • Multi-crosslinking composite hydrogel, dry powder of multi-crosslinking composite hydrogel, preparation method of dry powder and application of dry powder

    CN117624487A

  • High-toughness ionic liquid gel as well as preparation method and application thereof

    CN118638268A